Pharmacokinetics Of Recombinant Factor IX Fc Fusion Protein (rFIXFc) In Pediatric Subjects With Hemophilia B: An Interim Analysis Of The Kids B-LONG Study - Fischer, Kathelijn; Kulkarni, Roshni; Bradbury, Myles; Ragni, Margaret V.; Rangarajan, Savita; Dong, Yingwen; Li, Shuanglian; Jiang, Haiyan; Nugent, Karen; Pierce, Glenn F; Allen, Geoffrey (Blood, 2013)
Prophylaxis with factor IX (FIX) is the optimal treatment for patients with hemophilia B; however, due to the short half-life of currently available FIX products, frequent injections may be required to prevent bleeding episodes. To prolong half-life and reduce injection frequency, a long-acting recombinant FIX Fc fusion protein (rFIXFc) consisting of one rFIX molecule covalently linked to the Fc domain of immunoglobulin G1 (IgG1) was developed. In a phase 3 study in adults and adolescents, rFIXFc had a 2.43-fold increase in half-life and 50% reduction in clearance (CL) compared with FIX (BeneFIX®) (J Thromb Haemost. 2013;11[2]:241). The Kids B-LONG study (NCT01440946) was designed to evaluate the pharmacokinetics (PK), safety, and efficacy of rFIXFc prophylaxis in previously treated pediatric subjects with hemophilia B. The objective of this planned interim analysis was to determine the PK parameters of rFIXFc in subjects enrolled in Kids B-LONG and compare these parameters to their pre-study FIX PK parameters. This multicenter, open-label, phase 3 study is currently enrolling previously treated subjects aged<12 years with severe hemophilia B (≤2 IU/dL endogenous FIX), at least 50 exposure days (EDs) to FIX products, and no inhibitors to FIX. Subjects are stratified into two age cohorts (<6 and 6 to<12 years of age). A weekly prophylactic regimen of 50-60 IU/kg of rFIXFc is administered to all subjects, with subsequent dose and interval adjustments based upon PK data and bleeding frequency. Subjects will continue treatment until they achieve 50 EDs. The primary endpoint is the incidence of inhibitor formation. A sequential PK analysis is performed to compare the PK parameters of rFIXFc with that of pre-study FIX products. PK sampling of pre-study FIX occurs at baseline prior to first dose of FIX (50 IU/kg) and at 5 additional time points through 48 hours. PK sampling of rFIXFc occurs prior to first dose of 50 IU/kg rFIXFc and at 7 additional time points through 168 hours following the first dose; a washout period of 96 hours is required before the first dose of both pre-study FIX and rFIXFc. Plasma FIX activity is measured using the one-stage clotting assay calibrated against a commercially available FIX plasma standard and the FIX activity-over-time profiles are analyzed by non-compartmental analysis (NCA) using the PK data analysis software Phoenix™ WinNonlin 6.2.1.51. A data cut-off date of 23 April 2013 was used to report PK data in this interim analysis. At the time of this interim analysis, 24 subjects were enrolled and had received at least one dose of pre-study FIX and/or rFIXFc. Of 18 subjects with evaluable PK profiles, 15 had complete PK profiles for both pre-study FIX (BeneFIX®, Haemosolvex®, or Alphanine®) and rFIXFc. A comparison of PK parameters for rFIXFc versus FIX for both age cohorts is presented in Table 1. rFIXFc had a more than 3-fold prolongation in half-life and a more than 60% reduction in CL compared to the FIX products. Table 1PK of FIX products and rFIXFc in pediatric subjects (Geometric mean [95% CI])Half-life (hr)CL (mL/dL/kg)IR (IU/dL per IU/kg)Vss (mL/kg)< 6 yrsFIX (pre-study) n=518.1 (15.6 - 20.9)11.8 (9.27 - 15.0)0.525 (0.447 - 0.617)293 (247 - 348)rFIXFc (on-study) n=663.6 (42.1 – 96.2)4.36 (3.56 – 5.34)0.593 (0.494 - 0.711)344 (276 - 429)rFIXFc/FIX Ratio n=43.70 (2.56 - 5.34)0.385 (0.280 - 0.529)1.13 (0.981 - 1.31)1.21 (1.18 - 1.25)6 to<12 yrsFIX (pre-study) n=1317.8 (16.0 – 19.8)8.76 (7.35 - 10.5)0.638 (0.502 - 0.812)217 (165 - 286)rFIXFc (on-study) n=1370.4 (61.0 - 81.3)3.51 (3.01 – 4.09)0.718 (0.612 - 0.841)290 (237 - 354)rFIXFc/FIX Ratio n=113.99 (3.36 - 4.74)0.386 (0.322 - 0.462)1.16 (0.942 - 1.42)1.31 (0.992 - 1.74) In comparison to currently available FIX products, rFIXFc had a prolonged half-life and reduced CL in pediatric subjects, which was similar to previous observations in adults and adolescents. The final analysis of the Kids B-LONG study will provide further PK information and evaluate the safety and efficacy of rFIXFc in children. Fischer:Biogen Idec, Baxter, Novo Nordisk, Bayer: Membership on an entity's Board of Directors or advisory committees; Baxter, Bayer, Novo Nordisk, Pfizer: Research Funding. Kulkarni:Biogen Idec, Novo Nordisk, Baxter : Membership on an entity's Board of Directors or advisory committees. Ragni:Biogen Idec: Membership on an entity's Board of Directors or advisory committees; Bristol Myers Squibb, Smith Kline Glaxo, Tacere Benitec: Consultancy; Baxter, Bayer, Biogen Idec, Bristol Myers Squibb, CSL Behring, Merck, Novo Nordisk, Pfizer, Smith Kline Glaxo: Research Funding. Rangarajan:Baxter, Pfizer: Research Funding; Biogen Idec : Membership on an entity's Board of Directors or advisory committees. Dong:Biogen Idec: Employment, Equity Ownership. Li:Biogen Idec: Employment, Equity Ownership. Jiang:Biogen Idec: Employment, Equity Ownership. Nugent:Biogen Idec: Employment, Equity Ownership. Pierce:Biogen Idec: Employment, Equity Ownership. Allen:Biogen Idec: Employment, Equity Ownership.